The impact of book reading in the early years on parent–child language interaction. (March 2017) - Gilkerson, Jill; Richards, Jeffrey A; Topping, Keith J
Early language development predicts later reading competence, but does reading to young children enhance the language interaction between them and their parents? Automatic assessment of language interaction now yields adult word counts, conversational turn counts and child vocalization counts. This study had 98 families return reading activity logs for a day coinciding with automatic language analysis, and of these, 36 reported reading with their children aged 26–61 months on that day. Reading periods yielded much higher adult word counts and conversational turns than non-reading periods, indicating a greater degree of parent–child language engagement and interaction during reading periods. Such differences were not evident in child vocalization. Adult word counts and conversational turns were high during reading for both high and low education level mothers. Gender effects during reading were evident for adult word counts (but not conversational turns or child vocalization), indicating greater adult word counts with male children. These results have important implications for practical action by parents.